PSYCHOEDUCATION ON STUNTING ISSUES - Sugiarto, Angga; Sukini, Sukini; Maryani, Siti (Midwifery and Nursing Research, 2024)
Background: Stunting, defined as inadequate height for age, is a severe public health issue that affects millions of children worldwide, particularly in low and middle-income countries. It leads to long-term impacts on physical health, cognitive development, and economic productivity. Psychoeducation has been identified as a potential intervention to mitigate the effects of stunting by enhancing community and parental practices.Methods: This research is a pre-experimental study with a pre-post design. Measurements are conducted before and after the intervention. The population consists of all cadres in the Candiroto Community Health Center work area, and the sample size is 22 people. Statistical testing used the Wilcoxon test to determine the statistical differences before and after the psychoeducation.Results: The results indicate that there is a difference in knowledge and affective of the cadres regarding stunting issues.Conclusion: Psychoeducation is an effective intervention used as an approach for health cadres to understand and address stunting issues.